The antagonistic effect of caffeic acid phenethyl ester on cadmium‐caused pulmonary toxicity: MiR‐182‐5p/TLR4 axis - Rili Hao; Xing Zhou; Xiaqing Lv; Xiangyang Zhu; Yang Jiang; Dapeng Li (Food Frontiers, 2023)
Abstract Cadmium (Cd) is a heavy metal toxic that can cause health problems including lung injury. This study was set out to meet the growing demand for effective treatment of lung diseases and explore the mechanism of caffeic acid phenethyl ester (CAPE, a natural phenolic acid) protect against Cd‐caused lung damage. In this study, CAPE significantly increased mice body weight, decreased lung W/D ratio, and alleviated histomorphological injury. CAPE mitigated CdCl2‐induced oxidative stress through Nrf2/HO‐1/NQO1 pathway, suppressed inflammation via MyD88/NF‐κB pathway, and alleviated apoptosis by modulating apoptosis mediators. CAPE also inhibited the CdCl2‐caused decreasing of TLR4 level and the increasing of miR‐182‐5p level, which is achieved by miR‐182‐5p sponging TLR4. Collectively, miR‐182‐5p is involved in CAPE against CdCl2‐caused lung damage by targeting TLR4. MiR‐182‐5p/TLR4 is a new pathway for inhibiting oxidative stress, apoptosis, and inflammation in CAPE‐mediated lung protection, which provides a novel avenue for treatment therapies.